1975
DOI: 10.1073/pnas.72.10.4051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oncogenic virus on muscle differentiation.

Abstract: The question whether some events which control differentiation can modulate the course of viral-induced transformation is an important one and the answer to this question may throw some light on the mechanism of transformation as well as differentiation. There are several reports that cells in muscle cultures can be infected with either DNA or RNA viruses (1-6). However, muscle cultures, and even "muscle clones" consist of a heterogeneous population of cells in different compartments of the myogenic and fibrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
1

Year Published

1976
1976
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(71 citation statements)
references
References 27 publications
(31 reference statements)
11
59
1
Order By: Relevance
“…It also agrees with the lack of morphological changes in late-infected myotubes (Fig. 2d, e and f ) because the expression of the v-src protein would have caused a morphological deterioration in myotubes (Holtzer et al, 1975;pathway IV in Fig. 1 of Tanaka et al, 1992).…”
Section: Detection Of Viral Proteins In Late-infected Myotubes By Immsupporting
confidence: 85%
See 2 more Smart Citations
“…It also agrees with the lack of morphological changes in late-infected myotubes (Fig. 2d, e and f ) because the expression of the v-src protein would have caused a morphological deterioration in myotubes (Holtzer et al, 1975;pathway IV in Fig. 1 of Tanaka et al, 1992).…”
Section: Detection Of Viral Proteins In Late-infected Myotubes By Immsupporting
confidence: 85%
“…In this experiment, some of the early-infected myotube cultures had been shifted down to the permissive temperature (37 °C) prior to labelling. This procedure induced breakage of myotubes, as has been observed previously (Holtzer et al, 1975;Kobayashi & Kaji, 1978), but the profile of none of the radioactive viral proteins was significantly influenced by this temperature shift.…”
Section: Normal Amounts Of Radioactive V-sre and Env Proteins In Earlsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition to promoting tumor formation, anchorage-independent growth, and cellular immortalization, expression of transforming oncogenes inhibits cellular differentiation in several different cell lineages. In muscle cells, expression of oncogenic tyrosine kinases (v-src and v-fps), growth factor receptors (v-erbB), nuclear oncogene products (v-myc, c-myc, v-erbA, and E1A), and the activated forms of signal-transducing G proteins (H-ras and N-ras) can inhibit terminal differentiation to various extents (5,7,10,14,30,31,37,45). We previously demonstrated that ras and fos prevent myogenesis by inhibiting expression of MyoD (19).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a shift in the proliferative state of myoblasts, from a replicating population to a quiescent one, appears to be obligatory for myogenesis; the continued capacity to replicate is incompatible with myogenesis (7,11,15,21,23,24) and experimental manipulations which initiate DNA synthesis in differentiated cells reverse the myogenic phenotype (11,22,24). Thus the cessation and maintenance of suppression of DNA synthesis is a stringent requirement for skeletal muscle to develop.…”
mentioning
confidence: 99%